Pemilihan Kafe Terbaik Menggunakan Metode Cocoso Dan Perbandingan Moora - Nugraha, Agus; Lia Umbari Putri; Marpaung, Nasrun (Management of Information System Journal, 2025)
Choosing the best cafes in the range is a complex challenge considering a variety of criteria to be considered such as location, design, food and beverage quality, service, price, and facilities. To deal with this problem, two methods in the decision support system (SPK) are used, namely the CoCoSo method (Combined Compromise Solution) and Moora comparison (Multi-Objective Optimization on the basis of Ratio Analysis). In this study, the criteria used include location, design, food and beverage quality, service, price, and facilities. Each criterion is evaluated and weighed to determine the best alternative of the ten previously selected cafes. The process of normalization and criteria weighting is carried out to produce a final score that reflects the performance of each alternative based on the criteria that have been defined. The results of these two methods are compared to determine the best coffee in the range based on the criteria that have been established. This study shows that the use of CoCoSo and Moora methods provides reliable results in complex decision-making processes. In addition, this method can be widely applied in a variety of other fields to support better and informational decision-making.